The Time Famine: Toward a Sociology of Work Time - Perlow, Leslie A. (Administrative Science Quarterly, 1999)
This paper describes a qualitative study of how people use their time at work, why they use it this way, and whether their way of using time is optimal for them or their work groups. Results of a nine-month field study of the work practices of a software engineering team revealed that the group's collective use of time perpetuated its members' “time famine,” a feeling of having too much to do and not enough time to do it. Engineers had difficulty getting their individual work done because they were constantly interrupted by others. A crisis mentality and a reward system based on individual heroics perpetuated this disruptive way of interacting. Altering the way software engineers used their time at work, however, enhanced their collective productivity. This research points toward a “sociology of work time,” a framework integrating individuals' interdependent work patterns and the larger social and temporal contexts. The theoretical and practical implications of a sociology of work time are explored.